Venomous snakes and people in a floodplain forest in the Western Brazilian Amazon: Potential risks for snakebites. (November 2020) - Silva, Jéssica Lima da; Fonseca, Wirven Lima da; Mota da Silva, Ageane; Amaral, Gardênia Lima Gurgel do; Ortega, Givanildo Pereira; Oliveira, Andesson de Souza; Correa, Radraque Rodrigues; Oliveira, Igor; Monteiro, Wuelton Marcelo; Bernarde, Paulo Sérgio
Abstract: People who live in rural or forested areas are more likely to be affected by snakebites, due to their presence in the natural habitat of snakes and due to activities such as extractivism and agriculture. To conduct an ethnobiological study regarding the knowledge related to venomous snakes, snakebites and the attitudes of people who frequent areas of floodplain forests in the Alto Juruá (Brazilian Amazon), and correlate this information with data on snakebites in the region and the ecology of the ophiofauna, 100 residents, who are actively involved in extractivism, fishing, or hunting in the forests of the region were interviewed. Boards with photographs of venomous snakes from the region were used to ask questions about their experiences. The sampling of snakes was carried on trails in a forest used by residents of the region in their extractivism activities. Four venomous species ( Bothrops atrox, B. bilineatus smaragdinus, Micrurus lemniscatus and M. surinamensis ) were recorded. Among the interviewees, 31% claimed that they had already suffered at least one snakebite. The B. atrox snake is the species that the inhabitants encounter most and the one that is most associated with snakebites. Bothrops b. smaragdinus was the most common snake found during the search. Regarding accident prevention, 60% of them reported wearing boots when walking in the forest. In relation to practices adopted after a bite, the majority stated that they would seek medical attention; however, many reported using first aid measures that would not be medically effective for the victim's recovery. Despite B. b. smaragdinus being the most common snake found by researchers, it is responsible for very few snakebites. This is probably due to its arboreal habits, since it is found at a higher than average height (6.3 m) which is much higher than the height of a human being. The surveyed population demonstrated knowledge of the main preventive measures against snakebites, although some inadequate and/or ineffective first aid measures are still adopted. Highlights: The population practices activities in the forests which are related to snakebites. Four venomous species were recorded in the floodplain forest. Encounters between venomous snakes and the residents are relatively common. Bothrops atrox is the most common species and greatest cause of snakebites. Time constrained search is efficient for estimating the abundance of venomous snakes.